FORMULASI MUFFIN SUBSTITUSI TEPUNG PISANG KEPOK (Musa Paradisiaca Linn) DAN SUSU KEDELAI (Glycine Max) SEBAGAI ALTERNATIF PEMBERIAN MAKANAN TAMBAHAN ANAK SEKOLAH (PMT – AS) - Monika, Dwi; Syah R. Purba, Jonni (Poltekkes Kemenkes Pontianak, 2018)
Muffin as the kind of cake which was made in personal size, solid texture, clumped inside, and looks like a cupcake shape. In generally, muffin which was made by flour. However for utilizing the local food then can be replaced with banana flours. Soy milk was added in muffin making process. It aimed for increasing of nutritional value and as supplementary feeding alternative for student of elementary school. The aim of study was knowing the acceptability of color, aroma, flavor, texture and protein nutrition value from banana flour muffin with addition the differences of soy milk. The research was an experimental design with using the analysis of friedman test. There are three treatments of banana flour with soy milk F1 (90% : 0%), F2 (95% : 25%), F3 (100% : 50%). The result of organoleptic test showed that the best product was muffin with formula 100% : 50 % which was protein contains 6, 96 gram. This muffin has qualify of PMT-AS as 274,47 kkal, protein 6,96 gram per serving size. Based on the result showed that there was a significant by adding soy milk to protein level, aroma, texture and flavor of banana flour muffin. Researcher suggest or futher research is necessary to study for adding some of aroma varians from nature indrigient others for making banana flour subtitution muffin with adding soy milk is more preffered to student and society.